Opioid Use Disorder Increases 30-Day Readmission Risk in Inflammatory Bowel Disease Hospitalizations: a Nationwide Matched Analysis. (5th December 2019) - Charilaou, Paris; Mohapatra, Sonmoon; Joshi, Tejas; Devani, Kalpit; Gadiparthi, Chiranjeevi; Pitchumoni, Capecomorin S; Goldstein, Debra
Abstract: Background and Aims: The opioid epidemic has become increasingly concerning, with the ever-increasing prescribing of opioid medications in recent years, especially in inflammatory bowel disease [IBD] patients with chronic pain. We aimed to isolate the effect of opioid use disorder [OUD] on 30-day readmission risk after an IBD-related hospitalization. Methods: We retrospectively extracted IBD-related adult hospitalizations and 30-day, any-cause, readmissions from the National Readmissions Database [period 2010–2014]. OUD and 30-day readmission trends were calculated. Conventional and exact-matched [EM] logistic regression and time-to-event analyses were conducted among patients who did not undergo surgery during the index hospitalization, to estimate the effect of OUD on 30-day readmission risk. Results: In total, 487 728 cases were identified: 6633 [1.4%] had documented OUD And 308 845 patients [63.3%] had Crohn's disease. Mean age was 44.8 ± 0.1 years, and 54.3% were women. Overall, 30-day readmission rate was 19.4% [ n = 94, 546], being higher in OUD patients [32.6% vs 19.2%; p < 0.001]. OUD cases have been increasing [1.1% to 1.7%; p -trend < 0.001], while 30-day readmission rates were stable [ p -trend = 0.191]. In time-to-event EM analysis, OUD patients were 47% more likely (hazard ratio 1.47; 95% confidence interval [CI]:1.28–1.69; p < 0.001) to be readmitted, on average being readmitted 32% earlier [time ratio 0.68; 95% CI: 0.59–0.78; p < 0.001]. Conclusion: OUD prevalence has been increasing in hospitalized IBD patients from 2010 to 2014. On average, one in five patients will be readmitted within 30 days, with up to one in three among the OUD subgroup. OUD is significantly associated with increased 30-day readmission risk in IBD patients and further measures relating to closer post-discharge outpatient follow-up and pain management should be considered to minimize 30-day readmission risk.